Analisis Modal Kerja Terhadap Peningkatan Pendapatan Pada PT. Bulungan Tiga Putra Mandiri Desa Sanur Kecamatan Tulin Onsoi Kabupaten Nunukan Provinsi Kalimantan Utara (International Forum of Researchers and Lecturers, 2024)
Suriana. 2023. Analysis of Working Capital on Increasing Income at PT Bulungan Tiga Putra Mandiri. STIM-LPI Makassar Management Study Program Thesis (Supervised by Drs. Sabirin Iskandar, M. Si., and Dr. Khairina Rosyadah, S.E., M.M). This research aims to determine whether working capital increases income at PT. Bulungan Tiga Putra Mandiri. The object of this research is PT. Bulungan Tiga Putra Mandiri, a corporation which operates in the trading business of heavy systems and fruit peels. The data used is primary data. The sample in this research is the financial report of PT Bulungan Tiga Putra Mandiri for 3 years.The results of this research show that calculating financial data using activity ratio and profitability ratio analysis shows that the company's working capital at PT. Bulungan Tiga Putra is decreasing from 2020 to 2022, resulting in a decrease in income and even a loss.